Chemotherapy in Combination With Immune Checkpoint Inhibitors for the First-Line Treatment of Patients With Advanced Non-small Cell Lung Cancer: A Systematic Review and Literature-Based Meta-Analysis - Addeo, Alfredo; Banna, Giuseppe Luigi; Metro, Giulio; Di Maio, Massimo (Frontiers in Oncology, 2019)
Background: Checkpoint inhibitors plus platinum-based chemotherapy have shown superiority compared to chemotherapy alone as first-line therapy in advanced non–small cell lung carcinoma (NSCLC). To evaluate the relative benefit in term of Overall Survival (OS) and Progression-free Survival (PFS) of checkpoint inhibitors plus chemotherapy versus chemotherapy alone, overall and in subgroups defined by PDL1 expression we have performed a meta-analysis Data Sources This meta-analysis searched PubMed and checked references of the selected English language articles to identify further eligible trials. Data collection for this study took place from October 1 to October 24, 2018. Results In total, 8 trials involving 4646 patients with advanced NSCLC, 3.314 (71%) and 1.332 (29%) with a non-squamous and squamous histology, respectively, were included in this meta-analysis. Four trials used atezolizumab, 3 pembrolizumab and 1 nivolumab, accounting for 2.985 (64%), 1.298 (28%) and 363 (8%) of patients, respectively. The patients were randomized to receive first-line chemotherapy plus a checkpoint inhibitor versus first-line chemotherapy, 2978 patients for the OS endpoint and first-line chemotherapy plus a checkpoint inhibitor versus first-line chemotherapy, 1740 patients in the PFS endpoint. Checkpoint inhibitors plus chemotherapy were associated with prolonged OS, compared with chemotherapy in the ITT population (HR, 0.74; 95% CI, 0.64-0.87; p=0.0002, with significant heterogeneity among trials). Notably within the PDL1 low group (1-49) there was a significant heterogeneity (p=0.06) between type of drug and efficacy: the combination of chemotherapy plus pembrolizumab showed an OS benefit (HR, 0.56; 95% CI, 0.40-0.78; P<.00007) unlike the atezolizumab backbone trials (HR, 0.92; 95% CI, 0.62-1.37; P<0.69). However, checkpoint inhibitors plus chemotherapy were associated with prolonged PFS in the ITT (HR, 0.61; 95% CI, 0.56-0.66; P < 0.00001) and across PDL1 subgroups. Conclusion and Relevance Checkpoint inhibitors plus chemotherapy compared with chemotherapy, are associated with significantly prolonged OS and PFS in first-line therapy in NSCLC. In the low PDL1 subgroups the benefit was statistically significant only in the pembrolizumab backbone trials. The findings of this meta-analysis could assist in the design and interpretation of future trials and in economic analyses.